Case Analysis of Several Atypical Faults of Large Turbo-Generator Set - Xueyan ZHANG; Jie QU; Guoan HE; Pengbo ZHU; Guangzheng JIANG; Bo PAN (Zhongguo dianli)
This paper presents several atypical fault cases of large steam generator set caused by installation or maintenance mistakes in recent years. The fault symptoms, causes and consequences are described and analyzed in details, which involved axial displacement overrun, sudden change of turbine output and thermal parameters, or abnormal vibrations. The analytical procedures and experience of the cases can provide reference for the analysis of faults and accidents as well as the installation and maintenance guide of the unit in the future.